ANALYTICAL STUDY OF GROWTH OF THE MUTAL FUND INDUSTRY (International Journal of Food and Nutritional Sciences, 2022)
India has been ranked 7th in terms of nominal GDP, and in terms of mutual fund assets under management, the ranking of india is 17th. Less than 2% of the 1.3 billion people in the nation invest in mutual funds, compared to significantly larger percentages in industrialized economies such as the US.Mutual funds investments have have significantly increased over the last decades and have contributed to the growth of markets significantly (Anderson & Ahmed, 2005). The phenomenal growth in the Asset under management (AUM) has been witnessed in last decade years-from Rs. 5.9 trillion at the end of 2011-12 to 28 trillion crore at the end of 2020-21(Source AMFI Annual report 2021) shows a successful and bright story ahead for the mutual fund industry.Instead of being an asset management sector as described by international peers, the industry has transformed itself into a mutual fund industry. There is a chance to provide items that cater to various needs of investors. Increasing the adoption of products like ETFs and tapping into the management of pension and insurance funds are opportunities presented by global trends